Pembinaan dan pelatihan penulisan karya ilmiah di kalangan dosen Sekolah Tinggi Teologi Kadesi Yogyakarta - Talizaro Tafonao Talvin; Fransiskus Irwan Widjaja (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This community service activity aimed to improve the skills or knowledge of lecturers in writing scientific papers as an urgent need in the academic world. Method: The coaching and training were conducted to lecturers/partners of the Kadesi Yogyakarta Theological College. The method used was coaching and training in scientific article writing. Results: The results of this activity showed that there was an increase of about 70% after coaching and training were carried out using the lecture, question, and answer, discussion, and simulation methods. It can be seen from the enthusiasm of the partners when making the article outline. Conclusion: Coaching and training activities for writing scientific articles have a very positive impact on partners in fostering interest in writing scientific papers in online journals. Keywords: Coaching, Training, Lecturers, Trick of writing paper